Role of Dsg1- and Dsg3-Mediated Signaling in Pemphigus Autoantibody-Induced Loss of Keratinocyte Cohesion - Walter, Elias; Vielmuth, Franziska; Wanuske, Marie-Therès; Seifert, Matthias; Pollmann, Robert; Eming, Rüdiger; Waschke, Jens (Frontiers in Immunology, 2019)
2 ABSTRACT 3 Pemphigus is an autoimmune dermatosis in which mucocutaneous blisters are induced primarily 4 by autoantibodies against Desmoglein (Dsg) 1 and 3. Pemphigus vulgaris (PV) usually is 5 associated with autoantibodies against Dsg3 whereas pemphigus foliaceus (PF) patients present 6 autoantibodies against Dsg1. Several signaling pathways were proposed to cause loss of 7 keratinocyte adhesion. However, relevance of different signaling pathways and role of Dsg1 8 and 3 to trigger signaling are not fully understood. Here, we show that Ca2+ chelation reduced 9 PV-IgG- and PF-IgG-mediated loss of HaCaT keratinocyte cohesion whereas EGFR inhibition did not 10 inhibit effects of PF-IgG. PV-IgG activated EGFR in Src-dependent manner whereas both PV-IgG 11 and PF-IgG caused Ca2+ influx independent of EGFR. ERK activation was Src-dependent in 12 response to PV-IgG but not PF-IgG. To delineate the roles of Dsg isoforms to trigger signaling 13 pathways, Dsg3- and Dsg2-deficient HaCaT keratinocyte cell lines were generated using CRISPR/Cas9. 14 Dsg3- but not Dsg2-deficient cells were protected against PV-IgG-induced loss of cell adhesion. 15 Ca2+ influx and ERK activation in response to PF-IgG were preserved in both cell lines whereas 16 PV-IgG-induced ERK activation was abrogated in Dsg3-deficient cells.